The noncooperative provision of international environmental goods when countries differ in size - Carsten Schmidt (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
National reductions of CO2 emissions as a way to manage unilaterally the use of global environmental resources can be interpreted as the noncooperative provision of an international public good. This paper analyses two basic sources of inefficiency if countries abate their emissions noncooperatively. One is caused by the possibility to take a free ride on abatement activities of other countries, the second results from comparative cost advantages of emission abatements not being exploited. In a simple two-country, two-goods model it is analysed how asymmetries in population size influence the relative importance of these welfare losses by deriving for both an index of efficiency. The efficiency-properties of the Nash equilibrium are compared to the Stackelberg equilibrium.
Keywords: 330; Luftreinhaltung; Treibhausgas-Emissionen; Öffentliche Güter; Internationale Umweltpolitik; Spieltheorie; Wohlfahrtsanalyse; Theorie